2014
DOI: 10.4236/abb.2014.53027
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of far eastern species of the genus <i>Crepidostomum</i> (Trematoda: Allocreadiidae) by means of 28S ribosomal DNA sequences

Abstract: Genetic divergence and phylogenetic relationships of four species of the genus Crepidostomum Braun, 1900 sensu Caira, Bogĕa (2005) were revealed using partial sequences of 28S ribosomal RNA gene. Genetic divergence between C. cf. farionis (Muller, 1784) and C. nemachilus Krotov, 1959 was 3.1%, which corresponds to the mean value of interspecific divergence between Crepidostomum species. These two species, therefore, can be recognized as bonafide species. However, we found no genetic differences between 28S rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 23 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…Among allocreadiids from the Holarctic region, our results using the 28S rDNA gene corroborate the validity of the genus Megalogonia as proposed by Curran et al [ 16 ], and the paraphyletic condition of the Crepidostomum observed by Atopkin and Shedko [ 3 ], Pérez-Ponce de León et al [ 45 ], Petkevičiūtė et al [ 49 ], and Atopkin et al [ 5 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Among allocreadiids from the Holarctic region, our results using the 28S rDNA gene corroborate the validity of the genus Megalogonia as proposed by Curran et al [ 16 ], and the paraphyletic condition of the Crepidostomum observed by Atopkin and Shedko [ 3 ], Pérez-Ponce de León et al [ 45 ], Petkevičiūtė et al [ 49 ], and Atopkin et al [ 5 ].…”
Section: Discussionsupporting
confidence: 88%
“…New sequences obtained for the present study are in bold. Digeneans Host Host order Locality GenBank ID Reference 28S rDNA COI mtDNA Allocreadiidae Acrolichanus auriculatus Acipenser schrenckii ; Acipenser ruthenus ; Huso dauricus Acipenseriformes Russia MN524579 – MN524580 ; MN524583 ; MN524583 ; FR821397 – FR821398 [ 3 , 5 ] Allocreadium gotoi Misgurnus anguillicaudatus Cypriniformes Iiyama City, Japan LC215274 [ 59 ] Allocreadium isoporum Alburnus alburnus Cypriniformes Oster Lake, Karelia GU462125 – GU462126 …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, if we accept that the only species of the genus for which molecular data are available, C. funduli , from fundulids in USA, is actually a member of the genus (see contrary opinions in Manter, 1962; Brooks, 1976), then molecular phylogenetic analyses shed light on the paraphyly of Creptotrema . Other studies have already demonstrated, through molecular analyses of the 28S rRNA gene, cases of paraphyletic genera within Allocreadiidae, which contrast with the morphological concept on which these genera were erected (see Atopkin & Shedko, 2014; Pérez-Ponce de León et al , 2016; Petkevičiūtė, 2018). Recent molecular phylogenetic analyses of the Allocreadiidae show that the ‘papillose allocreadiids’ ( sensu Hopkins, 1937) do not form a monophyletic assemblage; oral lobes apparently either arose or were secondarily lost several times during the evolutionary history of the group, depending on the plesiomorphic condition (see Hernández-Mena et al ., 2016, 2019; Pérez-Ponce de León et al ., 2016; Atopkin et al ., 2020).…”
Section: Discussionmentioning
confidence: 97%
“…The distribution of these parasites coincides with the range of sturgeon (Skryabina, 1974;. Molecular-genetic data do not prove that C. auriculatum belongs to the Crepidostomum (Braun, 1900) genus (Atopkin & Shedko, 2014;Soldanova et al, 2017). The genus status of this parasite requires confirmation.…”
Section: Fig 3 Crepidostomum Auriculatum (Wedl 1858)mentioning
confidence: 90%